Pengaruh Mata Kuliah Baca Tulis Al-Qur’an Terhadap Peningkatan Kemampuan Baca Tulis Al- Qur’an Pada Mahasiswa PAI - Untung Khoiruddin (Institut Agama Islam Tribakti (IAIT) Kediri, 2022)
Al-Qur'an literacy education is one of the learning materials to direct students to the ability to read, write, understand, appreciate and make the Qur'an as a life guide. The ability to read and write the Qur'an is a skill possessed as a result of experience, education and training. This shows that the ability to read and write the Qur'an contains a learning dimension. Therefore, the importance of education in reading and writing the Qur'an in the ability of every human being to be able to read and write the Qur'an properly and correctly. This study aims to determine the effect of BTQ courses on the ability to read and write the Koran in PAI students batch 2018 at IAIN Kediri. This study uses quantitative methods with the type of correlation and regression research. The data collection technique uses a questionnaire with a population of 441 students, then a sample of 111 students is taken and the data analysis uses a simple linear regression test. And the results of this study indicate that there is a strong relationship between BTQ courses and the ability to read and write the Qur'an with a Pearson correlation value of 0.639 and there is an effect of reading and writing al- Qur'an courses on the ability to read and write the Qur'an. with the magnitude of the effect of 0.390 or 39%.